EXPLICIT INSTRUCTIONS FOR CREATIVE PERFORMANCE ACCORDING TO TWO CREATIVITY TESTS, TAKING INTELLIGENCE INTO ACCOUNT - Sanz de Acedo Lizarraga, María Luisa; Sanz de Acedo Baquedano, María Teresa (Anales de Psicología / Annals of Psychology, 2008)
The main purposes of the present study was to compare the impact of explicit creative instructions and noncreative general instructions on the performance in the Verbal Expression Test, Form A of the Torrance Tests of Creative Thinking (TTCT) and the “Test de Inteligencia Creativa” (CREA; in Spanish, the Creative Intelligence Test), as well as to determine whether the intelligence level—measured with the Domino Test, D-48—conditions creative activity and whether there is any interac-tion between the type of instructions and the intelligence level. The study was carried out with a sample of 341 high school students, of both sexes, and aged between 17 and 18 years. The results revealed that the explicit instructions for the creative performance of the tests activated responses in the experimental group that were significantly different from the responses of the control group to the same tests, following general instruc-tions, and this difference was more evident in high-intelligence subjects. Interesting conclusions for research, assessment, and education are reached.